Diagnosing Syndesmosis Instability: Dynamic Ultrasound versus Arthroscopy: A Cadaveric Study. Issue 4 (22nd October 2020) - Hagemeijer, Noortje; Sato, Go; Bhimani, Rohan; Lubberts, Bart; Elghazy, Mohamed Abdelaziz; Kerkhoffs, Gino; Guss, Daniel; DiGiovanni, Christopher W.
Category: Ankle Introduction/Purpose: To evaluate whether sagittal translation could be detected with ultrasound and arthroscopy and to compare the increasing tibiofibular sagittal translation seen with ultrasound (US) and Arthroscopy. Methods: Eight fresh lower leg cadaveric specimen amputated above the proximal tibiofibular joint were used in this study. The ankle syndesmosis was evaluated using a handheld US device (Butterfly iQ, Butterfly Network Inc, Guilford) and arthroscopy with intact-, and after sequent sectioning of anterior-inferior tibiofibular ligament (AITFL), interosseous ligament (IOL), and posterior- inferior tibiofibular ligament (PITFL). Sagittal plane translation was simulated with 100N of anterior to posterior (A-to-P) and posterior to anterior (P-to-A) hook force which was applied 5cm above of the ankle joint (Figure 1). Pearson's correlation, one- way repeated measures ANOVA, and Wilcoxon signed-rank test were used for comparison. Three cadavers were measured by two independent observers to assess reliability and analyzed using intraclass correlation coefficients (ICC). Results: A-to-P translation values obtained with US and Arthroscopy had a correlation of -0.14, and P-to-A translation correlation of 0.44. Using US, intact translation was 0.94+-0.62 with A-to-P hook and 0.87+-0.5 with P-to-A hook. Subsequent A- to-P and P-to-A translation increased with 0.07+-0.96mm and 0.04+-0.76 after AITFL cut, with 0.53+-0.9 and 0.15+-0.5 after IOL cut, and with 0.81+-1.3mm and 0.45+-0.8 after PITFL cut (p-values between 0.122 and 0.270) . Using arthroscopy, intact translation was 0.40 +-0.3 with A-to-P hook and 0.99+-0.5 with P-to-A hook. Subsequent A-to-P and P-to-A translation increased from intact with; 0.001+-0.3 and 0.30+-0.4 after AITFL cut, 0.19+-0.4 and 0.74+-0.7 after IOL cut, and 0.40+-0.5 and 1.1+-0.9 after PITFL cut (p-values between 0.005 and 0.037). No statistical differences between US and Arthroscopy were found. Conclusion: US was unable to differentiate between the different stages of injury, even though a similar increase in translation was seen as compared to arthroscopy. Probably this is due to the high variability seen in the US translation values. As US does have several advantages over arthroscopy; availability, non-invasiveness, low costs, and allowance of using the contralateral side as a direct comparison, this technique should be further explored as a potential diagnostic assessment technique of diagnosing occult syndesmotic instability in the sagittal plane.